2019
DOI: 10.1111/pace.13611
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac resynchronization therapy with His bundle pacing

Abstract: Aims:A novel therapy offering cardiac resynchronization therapy (CRT) with an additional lead placed in His bundle has been reported in a few case reports and case series as improving the hemodynamical and clinical condition of patients with permanent atrial fibrillation (AF) in whom other therapeutic methods have not been successful. Methods:Fourteen consecutive patients with permanent AF, heart failure (HF), bundle branch block (BBB) with QRS complex width >130 ms, and impaired left ventricular ejection frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 23 publications
10
41
0
Order By: Relevance
“…We observed better acute results in terms of ECG and echocardiographic outcomes on combining HBP with CS pacing (with or without concomitant RV pacing). Our results are consistent with those of others 35,36 . In a study by Vijayaraman et al 35 involving 27 patients, baseline QRS width was 183 ± 27 ms and significantly narrowed to 162 ± 17 ms during CONV, to 151 ± 24 ms during HBP, and further to 120 ± 16 ms during HBP + CS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed better acute results in terms of ECG and echocardiographic outcomes on combining HBP with CS pacing (with or without concomitant RV pacing). Our results are consistent with those of others 35,36 . In a study by Vijayaraman et al 35 involving 27 patients, baseline QRS width was 183 ± 27 ms and significantly narrowed to 162 ± 17 ms during CONV, to 151 ± 24 ms during HBP, and further to 120 ± 16 ms during HBP + CS.…”
Section: Discussionsupporting
confidence: 93%
“…HBP has been studied by some authors as an alternative to conventional CRT 30–34 and by others in conjunction with CS pacing 35,36 . In an acute hemodynamic study, His resynchronization delivered better ventricular resynchronization and greater improvement in hemodynamic parameters than biventricular pacing 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that 88.9% of the patients’ LVEF had been improved more than 50% over baseline at 1‐year follow‐up during HBP . In another prospective study showed that the use of atrial channel for HBP provided narrowing of QRS width and clinical improvement in left ventricular mechanical function …”
Section: Discussionmentioning
confidence: 97%
“…The updated ACC/AHA/HRS practice guideline suggested that using HBP and cardiac resynchronization therapy (CRT) is reasonable in patients with atrioventricular block as an indication for permanent pacing with an LVEF of 36%‐50% and expected ventricular pacing of >40% . Additionally, HBP may serve as an alternative therapeutic option in patients with bundle branch block and heart failure with reduced ejection fraction, which is a traditional indication for CRT . Left bundle branch block was successfully corrected with QRS duration narrowing with the use of HBP in a large number of patients recent study .…”
Section: Introductionmentioning
confidence: 99%